PRODUKSI BERAS DI INDONESIA - Hehamahua, Hayati (Fakultas Ekonomi, UIN Maliki Malang, 2008)
Crop product especially rice is on of strategic and important commodities in Indonesian economic. The growing needs of rice because of the increasing population from year to year. It seems that domestic rice need projection, as principal food from year to year will increase as explained by USDA in the Agricultural Baseline Projection report to 20014. Import projection showed that until 2014 the domestic need for rice will increase 22-25 tons along with population increase, that is expected will reach 253 populations in 2014 (with growth rate of 1.49% per year). This research based on secondary data that is related with research variable: land width, productivity, unhulled paddy, rice production, and rice import. The used analysis model to test this hypothesis is Structural Equation Modeling (SEM) The results by using SEM showed that (1) land influence significantly and positively toward rice production (2) land influence positively and positively productivity (3) productivity influence positively and significantly toward rice production (4) productivity influence the rice import, (5) and production influence the rice import.